2011
DOI: 10.2975/34.4.2011.304.310
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating in persons with serious mental illnesses: Understanding and barriers.

Abstract: This study revealed several modifiable barriers to healthy eating. Interventions that addressed these could aid in improving the diet and lowering the risk of cardiovascular disease in this population. Recommendations are to provide healthy eating education that is individualized, emphasizes the health consequences of poor eating, and provides opportunities to prepare and taste healthy foods. Family and friends should be included in all educational efforts. At community mental health centers and group homes, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 28 publications
2
68
0
3
Order By: Relevance
“…Looking at barriers to healthy eating, Barre, Ferron, Davis, and Whitley (2011) found internal factors (e.g., negative perceptions of healthy eating, decreased taste, difficulty changing habits, and mental health prioritization) and external factors (e.g., reduced availability, inconvenience of healthy foods, social pressures, and medication side effects) act as barriers to healthy eating. Our findings are consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at barriers to healthy eating, Barre, Ferron, Davis, and Whitley (2011) found internal factors (e.g., negative perceptions of healthy eating, decreased taste, difficulty changing habits, and mental health prioritization) and external factors (e.g., reduced availability, inconvenience of healthy foods, social pressures, and medication side effects) act as barriers to healthy eating. Our findings are consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…With poor engagement by mental health service users and such high attrition rates from targeted health programs, the modest effects of such programs become further limited as to their usefulness within the community population of mental health service users. Barriers to engagement and continuance with such programs have been explored [2428] and researchers have identified that symptoms due to illness, treatment side effects, stigma (structural, social, and self), receiving little support, and difficulties changing habits all act as significant barriers to healthier lifestyle choices for mental health service users. Authors have also, however, highlighted the need to explore facilitators and factors that might aid individuals and program development to potentiate health behavior change [25, 29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, people participating in a quit smoking group, pointed out professional support, the cost of cigarettes, instructions from a doctor and advice from friends as important motivators to quit smoking [23] rather than the health risks of smoking. Among people on anti-psychotic drugs, as many as 86% believed that the drugs were responsible [24] for their overweight, and in one weight loss program, barriers to weight loss were identified as difficulty changing familiar eating habits [25]. If a person places the responsibility of overweight on family and psychopharmacological interventions this affects health behavior expectations negatively, as the person might lose belief in his/her own capability to affect his/her own health, and therefore may adopt passive health behaviors.…”
Section: Introductionmentioning
confidence: 99%